A case study on the behaviors of blaan youth in Barangay Assumption, Koronadal City towards participating in the weaving industry - Lachica, Reana Ayn D.
In order to address the dwindling number of Blaan weavers, this study aimed to analyze the behaviors of Blaan youth in Barangay Assumption, Koronadal City, towards participating in the weaving industry. This descriptive case study used semi-structured interviews to gather data in situ. Interviews were conducted with four elder weavers selected purposively, and five younger weavers recruited through snowball sampling. The Theory of Planned Behavior was used to analyse the data. Behavior referred to weaving participation determined by attitude, subjective norms and perceived behavioural control (PBC). It was found that weaving was revived in the community as a cottage industry through the efforts of elder weavers who taught it to young Blaans through the Indigenous People’s Education Program (IPEd) in their elementary school. The younger weavers’ positive attitude was due to their appreciation of their textiles’ cultural significance; enjoyment from weaving; and pride for having a unique skill. While there is little social pressure (subjective norms), their family and friends’ favourable view on weaving motivates them. The extent of performing weaving (PBC) is enabled by the available resources for learning and practicing the craft provided in IPEd, at no cost. Additional funds for IPEd would increase the number of students in the weaving classes. Moreover, Blaan weavers who have learned the craft from their childhood through family members would participate more in the weaving industry, and would continue to do so if it turned into a sustainable income. The research concludes that weaving’s continuity is possible; however, more young Blaans would be motivated to participate in the weaving industry if they are given the infrastructural support they so need. For future studies, it is recommended that young non-weavers should be included as well.